Psychoactive substance use among psychiatric in-patients presenting to the Emergency Centre of a district hospital in Cape Town, South Africa. A retrospective descriptive study - Nardus Droomer; Paul Xafis; Philip Cloete (African Journal of Emergency Medicine)
Background: Mental illness and substance use are major global challenges, with their impact on Emergency Centres becoming evident, especially in South Africa. Patients facing these issues require significant resources from both hospital and community services. However, there is a lack of local data regarding the prevalence of concurrent mental health and substance use disorders. This study aims to evaluate the extent of psychoactive substance use within the psychiatric population at a District Hospital in Cape Town, South Africa. Methods: This study is a single-centre, retrospective descriptive analysis. It includes all patients referred to the inpatient psychiatric service over six months, recorded in an electronic database. Data were statistically analysed, considering the following variables: urine drug test results to identify specific substance (s) used, sex, age, diagnosis, and repeat visits. Results: A total of 597 patient visits were analysed. Fifty-nine percent tested positive for at least one substance. The patients’ average age was 34 years. A greater percentage of visits were for males (58 %), with males exhibiting a higher rate of positive test results (64 %) than females (51 %). Among the 146 repeat visits, a significant association was found between the number of visits and positive test results, with 73 % of patients with ≥2 repeat visits testing positive for substances (p < 0.001). Cannabis (60 %), methamphetamines (47 %), benzodiazepines (26 %), opioids (7 %), and cocaine (1 %) were the substances most frequently reported. Conclusions: Emergency Centres in South Africa are impacted by individuals seeking mental health care, and substance use significantly exacerbates these challenges. Substance use creates serious physical, mental, and social implications for patients. As emergency care practitioners and members of the broader healthcare system, we play vital roles in addressing these issues. This study provides valuable insights into the complexities of the situation and suggests potential approaches for intervention.